The Rise and Fall of Enforcement Institutions: An Example of Religion and Secularism - Pavel Ciaian; Jan Pokrivcak; d'Artis Kancs (Economics and Econometrics Research Institute (EERI), 2011)
Societies in Western civilisation enforce their rules through formal institutions such as secularism (SES), whereas in less developed civilisations often rely on informal institutions such as religion (RES). The present paper attempts to explain the determinants of societies' choice between different enforcement systems, and their implications for society development using an example of two different enforcement models: one informal (RES) and one formal (SES). We find that, because the RES is based on beliefs, its efficiency depends heavily on its credibility, making it little flexible and highly susceptible to conflicts in dynamic environments. In contrast, because under the SES societal rules are enforced through a formal legal enforcement sector, the SES is more flexible though also more costly than the RES. The empirical evidence strongly supports our findings that wealthy, dynamic and fast growing economies typically choose the SES for enforcing societal norms and rules.
Keywords: B15; E02; E11; O43; O44; P37; B52; Z12; Z13; 330; Enforcement institutions; economic growth; conflicts; religion; secularism